Sensitivity and Specificity of Dipstick Tests for Rapid Diagnosis of Malaria in Nonimmune Travelers - Jelinek, T. (American Society for Microbiology, 1999)
Swift diagnosis of Plasmodium falciparum malaria in areas where the disease is not endemic is frequently complicated by the lack of experience on the side of involved laboratory personal. Diagnostic tools based on the dipstick principle for the detection of plasmodial histidine-rich protein 2 (HRP-2) and parasite-specific lactate dehydrogenase (pLDH), respectively, have become available for the qualitative detection of P. falciparum malaria. In order to evaluate two of the currently available assays, specimens from 231 patients were screened during a prospective multicenter study. Among the screened specimens, samples from 53 patients (22.9%) were positive for P. falciparum malaria by microscopy and/or PCR. While the test kit based on the detection of HRP-2 performed with a sensitivity of 92.5% and a specificity of 98.3%, the kit for the detection of pLDH showed a sensitivity of 88.5% and a specificity of 99.4%. Dipstick tests have the potential of enhancing speed and accuracy of the diagnosis of P. falciparum malaria, especially if nonspecialized laboratories are involved.